The genus Sapromyza (Diptera: Lauxaniidae) in Iran with description of three new species - Namin, Saeed Mohamadzade; Gaimari, Stephen D. (Zootaxa, 2018)
Seventeen species of the genus Sapromyza Fallén occurring in Iran are revised. The following new species are described and illustrated: Sapromyza bernhardi, S. damavandensis and S. sabourii. In addition, S. clathrata Shatalkin, S. kabuli Papp and S. quadripunctata (Linnaeus) are recorded for the first time from Iran. Distribution of species in Iran is reviewed, and a key to the species is provided.